2019
DOI: 10.1590/rbz4820180021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of varying levels of dietary protein and net energy on growth performance, nitrogen balance and faecal characteristics of growing-finishing pigs

Abstract: This experiment was conducted to evaluate the effects of dietary protein and net energy (NE) levels on growth performance, nutrient digestibility, nitrogen metabolism, and faecal microbiota of growing-finishing pigs. Eighteen crossed barrows were randomly allocated into one of three dietary treatments: high protein + high NE diet, low protein + high NE diet, and low protein + low NE diet. The whole experiment lasted 90 days and was divided into three phases (phase I: 25-50 kg; phase II: 50-75 kg; phase III: 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 34 publications
6
14
1
1
Order By: Relevance
“…In the present study, as the dietary CP levels increased, a decreased serum TP was observed during the 5- to 10-kg growth stage (14–22% CP), while an increased serum albumin content was observed during the 20- to 30-kg growth stage (10–18% CP). These findings were contrary to those reported by Zhao et al ( 29 ), and the different dietary CP levels could be the reason for this difference.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the present study, as the dietary CP levels increased, a decreased serum TP was observed during the 5- to 10-kg growth stage (14–22% CP), while an increased serum albumin content was observed during the 20- to 30-kg growth stage (10–18% CP). These findings were contrary to those reported by Zhao et al ( 29 ), and the different dietary CP levels could be the reason for this difference.…”
Section: Discussioncontrasting
confidence: 99%
“…Besides, NH 3 -N is a substance that originated from the intestinal microbiota-fermented protein and AAs, and its serum concentration could also reflect the utilization of dietary protein. A lower serum NH 3 -N concentration was found in pigs fed with a lower CP diet ( 28 , 29 ). Therefore, the increased serum UN or NH 3 -N concentration combined with the impaired growth performance in the present study suggested an excessive dietary CP level.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In a similar study, Fang et al (2019) reported that feeding of low protein and high energy diet in crossbred (Duroc x Large White Yorkshire x Landrace) weaner pigs improved the growth performance. In another study, Zhao et al (2019) reported that 3.5% decreased in dietary protein than requirement did not affect the growth performance of growing-finishing pigs.…”
Section: Discussionmentioning
confidence: 91%
“…Зменшення вмісту харчового білка на 3,5 % не чинить несприятливого впливу на продуктивність росту та засвоюваність поживних речовин поросят [17].…”
unclassified